Development of a variable rate applicator for uniform fertilizer spreading - Han, Chelo-woo; Lee, Sang-yoon; Hong, Young-ki; Kweon, Giyoung (International Journal of Agricultural and Biological Engineering, 2019)
Environmental impact and economic concerns have driven a variable rate technology (VRT). Spinner spreaders were mainly used for granular fertilizer application since they are simple in design, inexpensive, and can cover large areas. However, the spreader was not adequate for VRT because uniformity changes drastically while varying application rates. Thus, the purpose of this study was to develop a variable rate applicator with uniform spreading patterns. A commercial spreader was modified with a controller and electric actuators for controlling fertilizer discharge directions and amounts. Database was established to determine the optimum discharge direction according to the fertilizer application amount. The uniformity of spreading patterns in accordance with the spread amount per set unit area was evaluated by the statistical coefficient of variation (CV) lower than 15% is assumed to prevent damage to the crop. Test results showed that CVs were 8%, 9%, and 8%, respectively, for a tractor in race track mode (adjacent passes in same direction of travel) at 200 kg/hm2, 300 kg/hm2, and 400 kg/hm2. This indicates that the fertilizer was spread uniformly, while the coefficient of variation was 12% at 200 kg/hm2 in back and forth mode (adjacent passes in the opposite direction of travel). Overall, the results suggest that the race track mode is suitable for operation of a tractor to ensure uniform spreading of fertilizer when applying at variable rates. The future goal is to establish a system for automatic variable rate application according to location in connection with soil analysis and geographic information systems. Keywords: variable rate technology, fertilizer application, uniform spreading, spinner, granular applicator, fertilizer amount control DOI: 10.25165/j.ijabe.20191202.3242 Citation: Han C-W, Lee S-Y, Hong Y-K, Kweon G-Y. Development of a variable rate applicator for uniform fertilizer spreading. Int J Agric & Biol Eng, 2019; 12(2): 82–89.